IMPACT OF ELECTRIC VEHICLES ON INDIAN DISTRIBUTION SYSTEM - Ankita Khandait, Yuvraj Chavhan, Krutika Gaikwad, Bramhadeo Wadibhasme (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicles driven by fossil fuel drastically increases green house gases and air pollution and uncontrolled air pollution is going to deplete ozone layer. For this all governments all over the world is trying to make publicity and promoting electric vehicles to low down percentage of carbon dioxide , carbon monoxide like poisonous gases emission in environment. In this well thought mathematical calculations and modelling and simulations of e-vehicles. The disadvantages associated like more losses, more voltage fluctions , excessive overloading and higher cost. So a reference model is made to design a complete electric vehicle.